Adipocytokines in Thyroid Dysfunction. (23rd June 2013) - Aydogan, Berna İmge; Sahin, Mustafa
Abstract : Adipocytokines are important mediators of interorgan crosstalk in metabolic regulation. Thyroid diseases have effects on metabolism and inflammation. The mechanism of these effects is not clear. Recently, there are several reports suggesting this interrelation between adipocytokines and thyroid dysfunction. In this review, we summarize this relation according to the literature.